Unravelling the combined effects of drought and nitrogen addition on carbon assimilation and reserves in Korean pine saplings - Tian, Jinyuan; Zhang, Hongxia; Wang, Anzhi; Wu, Jiabing; Rosner, Sabine; Zhu, Kai; Cai, Rongrong; Yuan, Fenghui (Frontiers in Plant Science, 2025)
Climate change profoundly impacts the physiological processes and adaptation strategies of plants. However, the physiological mechanisms of coniferous species responding and adapting to combined drought and nitrogen (N) addition remain unclear. Here, based on 2-year multi-level N addition and drought experiments, we investigated the responses of carbon assimilation (net photosynthetic rate An, stomatal conductance gs and intrinsic water use efficiency WUEi) and carbon reserves (non-structural carbohydrates, NSC) of 7-year-old Korean pine (Pinus koraiensis) saplings. Our results showed that: (1) Drought decreased An and gs, while N addition increased An and decreased gs. N addition decreased An and WUEi but increased gs in plants under drought conditions, indicating that N addition under drought stress will maintain gas exchange by increasing stomatal opening, but failed to mitigate the reduction of An. (2) Both drought (moderate and severe) and N addition reduced leaf NSC concentrations. Under moderate drought stress, however, N addition led to an increase in leaf NSC concentrations. (3) The interconversion between leaf starch and soluble sugars slowed the decrease in carbon assimilation caused by drought. P. koraiensis saplings adopted a conservative strategy of increasing leaf mass per area (LMA) to adapt to reduced water use efficiency. The study highlights the coordinated relationship between carbon assimilation and carbon reserves of Korean pine saplings under combined drought and N addition, which improves our understanding of the diverse carbon dynamics of different species under climate change.